2018
DOI: 10.1680/jsmic.18.00005
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic cementitious construction materials for next-generation infrastructure

Abstract: The resilience of civil engineering structures has traditionally been associated with the design of individual elements with sufficient capacity to respond appropriately to adverse events. This has traditionally employed ‘robust’ design procedures that focus on defining safety factors for individual adverse events and providing redundancy. As such, construction materials have traditionally been designed to specific technical specifications. Furthermore, material degradation is viewed as inevitable and mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In the UK, the Resilient Materials for Life project led by Cardiff University in partnership with the universities of Cambridge, Bath and Bradford, have developed four self-healing techniques; the use of microcapsules containing mineral healing agents, bacterial healing, the use of a shape memory polymer based system for crack closure and the delivery of a mineral healing agent through a vascular flow network. They observed that all four techniques showed significant results of accelerated crack healing in the range of 14-28% and the Whole-Life Costing (WLC) analysis indicated a ∼12% reduction in the cost of repairs and maintenance (Teall et al, 2016;Al-Tabbaa et al, 2018, 2019Davies et al, 2018). However, the microencapsulation technique did not show a significant effect on the compressive strength.…”
Section: Bioconcretementioning
confidence: 99%
“…In the UK, the Resilient Materials for Life project led by Cardiff University in partnership with the universities of Cambridge, Bath and Bradford, have developed four self-healing techniques; the use of microcapsules containing mineral healing agents, bacterial healing, the use of a shape memory polymer based system for crack closure and the delivery of a mineral healing agent through a vascular flow network. They observed that all four techniques showed significant results of accelerated crack healing in the range of 14-28% and the Whole-Life Costing (WLC) analysis indicated a ∼12% reduction in the cost of repairs and maintenance (Teall et al, 2016;Al-Tabbaa et al, 2018, 2019Davies et al, 2018). However, the microencapsulation technique did not show a significant effect on the compressive strength.…”
Section: Bioconcretementioning
confidence: 99%
“…A national UK team, from the universities of Cambridge, Cardiff and Bath, has come together, through research council funding, to develop the first generation of self-healing cementitious systems in the UK to address cracks across many length scales [31][32][33]. This led to the development of a suit of complementary technologies namely microcapsules, calcite precipitation bacteria, shape memory polymer tendons and vascular networks (Fig 1b).…”
Section: Large-scale and Field Application Of Self-healing Concretementioning
confidence: 99%
“…The self-healing ability of cementitious systems can be enhanced by engineered additions of external healing agents, and this usually depends on the crack size and the nature of the cementitious matrix [6] as shown in Figure 1 [7]. Enhanced autogenous healing can be facilitated through non-encapsulated additions which include fibers, mineral or crystalline additives and superabsorbent polymers.…”
mentioning
confidence: 99%
“…Autonomic self-healing systems developed for cementitious materials, depending on the crack size[7].…”
mentioning
confidence: 99%